Edukasi Pemurnian Logam Tembaga melalui Elektrolisis untuk Siswa SMA Terpadu Wira Bhakti Gorontalo - Sukamto, Kostiawan; Lukum, Astin; La Kilo, Akram; Kunusa, Wiwin Rewini (Damhil: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service activity aims to provide students at SMA Terpadu Wira Bhakti Gorontalo with an understanding of the copper purification process through electrolysis and the application of environmentally friendly technology in the metallurgy industry. The activity was carried out using a combined approach of theoretical instruction and direct laboratory practicum. Students learned the basic principles of electrolysis, the mechanism of copper purification, and how this technology reduces environmental impact compared to traditional methods. During the practicum, students had the opportunity to apply the theory they had learned, observe the electrolysis process, and understand the results of copper purification. The evaluation results indicate that the activity was effective in enhancing students' understanding of electrolysis and the importance of sustainable technology in the industry. Additionally, the activity successfully sparked students' interest in the field of engineering and environmentally friendly industries.